Detection of Retinal Nerve Fiber Layer Defects in Alzheimer’s Disease Using SD-OCT - Kromer, Robert; Serbecic, Nermin; Hausner, Lucrezia; Aboul-Enein, Fahmy; Froelich, Lutz; Beutelspacher, Sven (Frontiers in Psychiatry, 2014)
Introduction: To examine the clinical value of spectral-domain optical coherence tomography (Spectralis OCT) to detect retinal nerve fibre layer defects in patients with clinically defined Alzheimer‘s disease (AD). Material and Methods: This cross-sectional study included 22 patients with AD (mean age: 75.9 ± 6.1 years) and 22 healthy age- and sex-matched controls. Neuro-ophthalmologic examinations and a series of high-resolution OCT examinations of the peripapillary retinal nerve fibre layer (RNFL) thickness using the Spectralis 3.5-mm circle scan protocol with ART-Modus and eye tracking were obtained, and compared to age- and sex-matched healthy control subjects. Results: Patients with AD showed a significant decrease in RNFL thickness in the nasal superior sector compared to the control group (101.0 ± 18.18 µm vs. 122.8 ± 28.08 µm; p